Using Quizizz as an Interactive Learning Media to Improve Cognitive Values in Elementary School Students - Narawati, Arlina Yuli; Supriadi, Didi; Mulyanto, Rahmat (International Journal of Engineering, Science and Information Technology, 2025)
Learning is a complex process that occurs in a person's life. If there is contact between humans and their environment, individually or in groups, then learning will occur. Students use learning media as an intermediary tool to convey messages or information. Creative media can stimulate students' interest in the lesson. This study aims to investigate the application of quizzes in the digital era's learning process and assess their impact on enhancing students' cognitive values. This study uses a research and development method. Research indicates that to support the teaching and learning process effectively, web-based, application-based learning media must meet the standards of validity, practicality, and effectiveness. In this case, Quizizz, the developed learning medium, underwent material validation and technical evaluation stages to ensure that the presented content aligned with the curriculum and learning objectives. This validation also encompasses the suitability of the material's content and the application's user-friendliness. In addition to the validity aspect, the practicality of the media is also an essential factor in this assessment. Based on the observations and user responses, students and teachers responded positively to Quizizz as a learning medium. The ease of access and use of the available features, such as interactive questions and various quiz modes, make learning more engaging and not boring. This shows that Quizizz is practical and can increase students' interest in learning through a more dynamic approach. Finally, the effectiveness of Quizizz as a learning medium is evident in the results of observations and responses from students and teachers during the learning process. Students looked more enthusiastic and motivated to actively participate in the quizzes, which helped them understand the material better. The provided results analysis feature also aids teachers, enabling more accurate assessment of student learning outcomes. Quizizz is a valid, practical, and effective medium for interactive learning.